Faktor-Faktor Kendala Dalam Pencatatan Keuangan Pada UMKM Toko Sembako - Fitria Puteri Sholikah; Puji Iswanto; Neni Sumarni (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This study aims to determine the problems of financial records in micro, small and medium business units because the MSME sector is currently very helpful to the community's economy as business actors. This type of research uses descriptive qualitative research. This method describes objects according to reality as they are. Data collection techniques are carried out in a triangulation manner using different data collections to obtain data from the same data source. The business actors in Telukjambe where the four basic food shop businesses are known to have their own uniqueness in developing their business, but this is from the results that have been researched on a sample of the four basic food shops in Telukjambe Karawang still not doing financial records properly, accounting is practiced only in the mind/ memory. The practical form of applying financial records to MSMEs has been carried out, there are two ways that can be applied to these basic food shops with an excel-based financial reporting system and simple financial reporting. The benefits of these two forms of accounting are at least being able to analyze the company's performance so that the future direction is predicted for the sustainability of the business being built so that business actors do not experience losses.